2009
DOI: 10.1590/s0034-70942009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of the Alveolar Recruitment Maneuver on Blood Oxygenation during Bariatric Surgery

Abstract: Alveolar recruitment maneuver with sudden increase of PEEP to 30 cmH2O showed a better response of the PaO2/FiO2 ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The study by Souza et al [23] compared the use of RM with progressive PEEP of 10, 15 and 20 cmH 2 O versus CPAP 30 cmH 2 O and found that the RM with progressive PEEP obtained lower mean airway pressures, p = 0.0003, (MD -7.40, 95% CI − 11.45 to − 3.35; participants = 33; studies = 1; I 2 = 0%).…”
Section: Alveolar Recruitment Maneuver Plus Peep 10 15 and 20 Versusmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Souza et al [23] compared the use of RM with progressive PEEP of 10, 15 and 20 cmH 2 O versus CPAP 30 cmH 2 O and found that the RM with progressive PEEP obtained lower mean airway pressures, p = 0.0003, (MD -7.40, 95% CI − 11.45 to − 3.35; participants = 33; studies = 1; I 2 = 0%).…”
Section: Alveolar Recruitment Maneuver Plus Peep 10 15 and 20 Versusmentioning
confidence: 99%
“…Three studies [21,23,24] compared alveolar recruitment maneuvers (RM) versus PEEP to evaluate intra operative gas exchange, with the mean PaO 2 /FiO 2 ratio found to be greater in the groups that underwent RM, p = 0.03, (MD 79.93, 95% CI 8.83 to 151.04; participants = 121; studies = 5; I 2 = 80%,). Figure 3 shows the comparison of three different studies, separate in four subgroups, where the best results were in favor of RM Fig.…”
Section: Effects Of Interventions Alveolar Recruitment Maneuvers Versmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the literature suggests that it should be initiated immediately after or up to the 30th minute following induction and then continued throughout the operation. 2,33 In our study, the mean duration of the surgery was 55 6 4.59 minutes for each rabbit. PEEP was initiated at induction and was continued throughout the surgery.…”
Section: Discussionmentioning
confidence: 76%
“…This relationship was explored in the study by Souza et al, (25) which demonstrated that the technique of ARM with sudden increases in PEEP to 30cmH 2 O resulted in the best response in the PaO 2 /FiO 2 relationship compared to the gradual increase of PEEP. However, Futier et al compared a ventilatory strategy associated with the use of ARM in healthy and obese subjects undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%